2019
DOI: 10.1093/gerona/glz210
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C-Reactive Protein for Bacterial Infection Diagnosis in Elderly Patients After Traumatic Orthopedic Surgery

Abstract: Background Biomarkers prove valuable for diagnosing postoperative bacterial infection, but data in elderly patients are scarce. Here we analyze how procalcitonin and C-reactive protein (CRP) perform for bacterial infection diagnosis after traumatic orthopedic surgery in elderly patients. Methods We included all patients admitted to our perioperative geriatrics unit after traumatic orthopedic surgery. Patients on antibiotics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…e main reason for infection in open wounds is that the skin at the fracture site is damaged, which leads to the contact between the surrounding tissues at the fracture site and the outside world, and the continuous invasion of pathogenic microorganisms, leading to the occurrence of related infection after surgery [3]. Incidence of postoperative infection patients in a clinical study showed that wound healing time, hospitalization time, and the incidence of infection related complications are significantly higher than noninfectious patients; wound healing and longer duration of hospitalization not only bring physical discomfort to patients but also increase the hospitalization time and hospitalization cost, causing certain economic burden to patients [4,5]. erefore, reducing the postoperative infection rate can not only effectively accelerate wound healing but also reduce the length of hospital stay and medical expenses [6].…”
Section: Introductionmentioning
confidence: 99%
“…e main reason for infection in open wounds is that the skin at the fracture site is damaged, which leads to the contact between the surrounding tissues at the fracture site and the outside world, and the continuous invasion of pathogenic microorganisms, leading to the occurrence of related infection after surgery [3]. Incidence of postoperative infection patients in a clinical study showed that wound healing time, hospitalization time, and the incidence of infection related complications are significantly higher than noninfectious patients; wound healing and longer duration of hospitalization not only bring physical discomfort to patients but also increase the hospitalization time and hospitalization cost, causing certain economic burden to patients [4,5]. erefore, reducing the postoperative infection rate can not only effectively accelerate wound healing but also reduce the length of hospital stay and medical expenses [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tibial plateau leveling osteotomy is a standard therapy for dogs with CCL rupture, a common condition in large‐breed dogs 29 . Compared with other orthopedic surgeries, the reported complication rate is relatively high, ranging from 11 to 34% 10–12 . Prediction or early detection of SSI via a biomarker would be of immense value and support prudent antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, in another study, PCT had similar or lower diagnostic accuracy than other biomarkers, such as C-reactive protein (CRP), with a sensitivity of <80%, for predicting bacterial surgical site infection after orthopedic surgery. 12 One of the most common surgical procedures used to treat canine cranial cruciate ligament (CCL) rupture is the tibial plateau leveling osteotomy (TPLO). 13 The procedure is normally preceded by confirmation of CCL rupture via arthroscopy under the same anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic and prognostic value of PCT elevation in geriatric patients on hospital admission has been investigated by several studies in the pre-COVID-19 era, with conflicting results [17][18][19][20][21][22][30][31][32][33][34]. Some of these studies have concluded that PCT elevation in older patients is significantly associated with bacterial pneumonia, sepsis, severity of infection, and mortality [20-22, 30, 31].…”
mentioning
confidence: 99%
“…Some of these studies have concluded that PCT elevation in older patients is significantly associated with bacterial pneumonia, sepsis, severity of infection, and mortality [20-22, 30, 31]. Other studies, instead, underlined that the diagnostic and prognostic performance of PCT elevation in these patients is nonsuperior and in some cases deliberately inferior, to that of serum CRP [19,[32][33][34], which is generally considered as the inflammatory biomarker guiding therapeutic choices in acute geriatric patients [35,36]. Therefore, PCT elevation was basically regarded as a marker of inflammation or infection in older patients and not as a reliable diagnostic or prognostic indicator [34].…”
mentioning
confidence: 99%